Revelation and Political Philosophy: What Is Islamization of Knowledge? (American Journal of Islam and Society, 1993)
This is a "work in progress" presentation based on mearch I am nowconducting about the development of Islamic political philosophy duringthe classical period of Islam. My contention is that a better understandingof that tradition puts the current debate about Islamic fundamentalism orresurgence into a new perspective. Behind the sensational, popular demandsfor greater adherence to the strictures of the revealed law of Islamlies an issue of fundamental importance: how divine revelation is to beunderstd and interpreted for political guidance. Those who developedIslamic political philosophy spoke directly to this issue and did so in amanner that merits the attention of contemporary Muslim activists, scholarsinterested in Islam, and thoughtful human beings in general. Theythought clearly about the relationship between religious belief andpolitical practice because they addressed the issue ditectly and withoutpreconceptions. Consequently, whatever our religious and cultural origins,we can benefit greatly from their teaching.One of my goals is to refocus current social science scholarship whileengaging Muslim scholars in debate on topics they deem urgent. Lately,there have been many, perhaps too many, reports and prognostics concerningthe success of resurgent Islam as well as the challenges it posesto Middle Eastern and western regimes. Such studies invariably talkabout, rather than with, those calling for greater attention to Islamic preceptsand practices; they presuppose and reinforce an attitude of "us" and"our valued' vetSUS "them" and "their values." Such a posture not onlyfosters antagonism and misunderstanding, it also ignores the way Muslimsare now addressing this complex phenomenon.Indeed, for almost a decade, Muslims trained in the West have beeninvestigating how western learning, especially the social sciences, illuminatestraditional Islamic sciences and vice versa. This task addresses, atthe highest level, the issue behind the call for application of the Shari'ahand offers the best Contemporary possibility of achieving some kind ofintercultural understanding. It offers those interested in western and Islamicculture a unique opportunity to delve mare deeply into another cultureand thereby understand the other and their own culture better.Another goal is to investigate how philosophers within the classicalperiod of Islam understood revelation and its outward manifestationprophecy-to influence political life. While mast scholars recognize the ...